2019
DOI: 10.2478/hukin-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mechanical Midsole Characteristics of Running Shoes Do Not Influence Physiological Variables in Aerobic and Anaerobic Running

Abstract: The purpose of this study was to determine the influence of footwear stiffness and energy loss on oxygen uptake and heart rate in athletes running under aerobic and anaerobic conditions. Four footwear conditions with identical outsoles, insoles, upper materials, but different mechanical properties regarding polyurethane midsole materials were investigated. Respective midsole material characteristics were selected to represent a wide range of running shoes. The test procedure for eighteen well‐trained male runn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…For example, Fuller et al (2016) suggested that apart from shoe mass, other factors not analyzed in the current study, may influence RE (i.e., shoe cushioning). However, previous research reported similar VO 2 and HR values in runners using shoes with different midsole characteristics but with similar shoe mass (Mitschke et al, 2019), indicating that shoe mass may be the most relevant variable when analyzing the influence of footwear on RE. In addition, the TTE was performed after the submaximal test (warm-up), and therefore, the participants could have accumulated fatigue that may have affected the TTE test performance.…”
Section: Limitationsmentioning
confidence: 86%
“…For example, Fuller et al (2016) suggested that apart from shoe mass, other factors not analyzed in the current study, may influence RE (i.e., shoe cushioning). However, previous research reported similar VO 2 and HR values in runners using shoes with different midsole characteristics but with similar shoe mass (Mitschke et al, 2019), indicating that shoe mass may be the most relevant variable when analyzing the influence of footwear on RE. In addition, the TTE was performed after the submaximal test (warm-up), and therefore, the participants could have accumulated fatigue that may have affected the TTE test performance.…”
Section: Limitationsmentioning
confidence: 86%
“…On the contrary, when considering the perspective of kinematics, it is important to note that the applicability of MBT shoes is restricted to specific scenarios or individuals, rather than being generally suitable for every person. In contrast, the frontal plane is responsible for the most notable alterations in the kinematics of the lower limbs during walking and running ( Gu et al, 2014 ; Mei et al, 2015 ; Mitschke et al, 2019 ). This is due to its resemblance to the structure of a barefoot and its consequential influence on biomechanical outcomes.…”
Section: Introductionmentioning
confidence: 99%